2013
DOI: 10.1007/s12149-013-0706-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of atherosclerosis in oncologic patients using 18F-fluoride PET/CT

Abstract: Our results suggest that (18)F-fluoride PET/CT might be a useful modality for detecting active mineral deposition sites of atherosclerosis in oncologic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Since 18 F-NaF is taken up at sites of calcification, another interesting potential application may be in the assessment of atherosclerosis (49). In fact, use of PET with 18 F-FDG and 18F-NaF may provide important insight into the evolutionary phases of the atherosclerotic plaque from a vulnerable inflammatory state to development of plaque microcalcification, which then helps to understand the complex biology of plaque rupture (50).…”
Section: Benign Bone Joint and Other Diseasesmentioning
confidence: 99%
“…Since 18 F-NaF is taken up at sites of calcification, another interesting potential application may be in the assessment of atherosclerosis (49). In fact, use of PET with 18 F-FDG and 18F-NaF may provide important insight into the evolutionary phases of the atherosclerotic plaque from a vulnerable inflammatory state to development of plaque microcalcification, which then helps to understand the complex biology of plaque rupture (50).…”
Section: Benign Bone Joint and Other Diseasesmentioning
confidence: 99%
“…There have already been several studies investigating the usefulness of NaF-18 PET for bone metastases (1,12,13), atherosclerosis (6,7,15), meningioma (22), and so on. In addition, several studies have compared Tc-99m-labeled bone scintigraphy and NaF-18 PET (11,14,19).…”
Section: Zusammenfassungmentioning
confidence: 99%
“…In the same study we also found that hypercholesterolemia, particularly high levels of total cholesterol and LDL-C, were significantly associated with aggressive metastatic PCa with an OR of 3.28 [137]. Recent studies indicated that hypertension, hypercholesterolemia, atherosclerosis, and a composite score of metabolic factors were associated with advanced PCa, biochemical recurrence and increased tumor mortality [28,93,139,148,149,150,151], as shown in Figure 2.…”
Section: Resultsmentioning
confidence: 88%